2016
DOI: 10.1111/jcmm.13053
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy: an adaptive physiological countermeasure to cellular senescence and ischaemia/reperfusion‐associated cardiac arrhythmias

Abstract: Oxidative stress placed on tissues that involved in pathogenesis of a disease activates compensatory metabolic changes, such as DNA damage repair that in turn causes intracellular accumulation of detritus and ‘proteotoxic stress’, leading to emergence of ‘senescent’ cellular phenotypes, which express high levels of inflammatory mediators, resulting in degradation of tissue function. Proteotoxic stress resulting from hyperactive inflammation following reperfusion of ischaemic tissue causes accumulation of prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 101 publications
(172 reference statements)
0
50
0
3
Order By: Relevance
“…Autophagy is an evolutionarily conserved pathway that targets cytoplasmic contents (eg, organelles or protein aggregates) to the lysosome for degradation . Although some controversies exist, most reports in the literature show insufficient autophagy during DCM .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Autophagy is an evolutionarily conserved pathway that targets cytoplasmic contents (eg, organelles or protein aggregates) to the lysosome for degradation . Although some controversies exist, most reports in the literature show insufficient autophagy during DCM .…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is an evolutionarily conserved pathway that targets cytoplasmic contents (eg, organelles or protein aggregates) to the lysosome for degradation. 4,5,36 Although some controversies exist, most reports in the literature show insufficient autophagy during DCM. [37][38][39][40] Our previous study also indicated that cardiomyocyte autophagy was downregulated as evidenced by decreased LC3-II expression and increased p62/aggresome accumulation in the diabetic heart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Згідно з вільнорадикальною теорією, у процесі старіння відбувається наростання молекулярних пошкоджень мембран і генетичного апарату клітини, послаблення активності захисних механізмів (Josq Maryn-Garcya, 2005;Hayat, 2014;Lekli et al, 2017). Одна з основних причин такого явищаінтенсивна генерація активних форм оксигену.…”
Section: вступunclassified
“…Надлишкове утворення перекисних продуктів викликає накопичення дисфункціональних і аномальних мітохондрій, що визначається важливою патофізіологічною особливістю старіння серця (Ikeda et al, 2014;Zhao et al, 2014). У похилому віці знижується ефективність репараційних процесів, а саме аутофагія / мітофагія, тобто видалення пошкоджених, не функціональних мітохондрій (Hayat, 2014;Lekli et al, 2017).…”
Section: обговоренняunclassified